Increased Plasma β‐Secretase 1 Activity Correlates With Neurodegeneration in Cerebral Small Vessel Disease - Ya Su; Qiong Wang; Feng Gao; Jiajie Xu; Jiayu Fu; Yunqing Ying; Yiwei Xia; Xiaoxiao Wang; Qiang Dong; Yong Shen; Xin Cheng (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background β‐secretase 1 (BACE1) plays a key role in amyloidogenic pathway and is considered a new mechanism for cerebral small vessel disease (CSVD). We explore the potential role of plasma BACE1 in CSVD and the pathological process it may be involved in. Methods and Results We enrolled 163 participants with CSVD (114 cerebral amyloid angiopathy and 49 hypertensive hemorrhage), and 96 cognitively unimpaired elders and 40 participants with Alzheimer's disease as controls. We measured BACE1 activity using a synthetic fluorescence substrate enzyme‐linked immunosorbent assay. We used regression models to investigate associations between BACE1 and imaging and blood markers as well as clinical outcomes in CSVD. Plasma BACE1 activity was significantly higher in CSVD (median 862.0 relative fluorescence units [RFU], interquartile range 700.6–1032.9) compared with elder controls (522.5 RFU, 438.3–662.1, P<0.001) but lower than Alzheimer's disease (964.0 RFU, 838.4–1225.0, P=0.032). For CSVD, there was an association between plasma and cerebrospinal fluid BACE1 activity (β=0.50, P=0.030). Plasma BACE1 activity was negatively associated with hippocampal volume (coefficient −2.40, P<0.001), and positively associated with blood neurofilament light chain (coefficient 0.08, P<0.001) and total tau (coefficient 0.15, P=0.006) but not with specific cerebrovascular imaging markers. During 2‐year follow‐up, BACE1 activity was independently related to dementia conversion (odds ratio, 17.72; P=0.001) but not stroke in CSVD. Conclusions Plasma BACE1 activity is moderately increased and associated with neurodegeneration and cognitive impairment risk in CSVD. It indicates that BACE1 is a promising biomarker especially for CSVD‐related neurodegeneration.